Performance, Emissions, and Combustion Characteristics of a Hydrogen-Fueled Spark-Ignited Engine at Different Compression Ratios: Experimental and Numerical Investigation - Ducduy Nguyen; Tanmay Kar; James W. G. Turner (Energies, 2023)
This paper investigates the performance of hydrogen-fueled, spark-ignited, single-cylinder Cooperative Fuel Research using experimental and numerical approaches. This study examines the effect of the air–fuel ratio on engine performance, emissions, and knock behaviour across different compression ratios. The results indicate that λ significantly affects both engine performance and emissions, with a λ value of 2 yielding the highest efficiency and lowest emissions for all the tested compression ratios. Combustion analysis reveals normal combustion at λ ≥ 2, while knocking combustion occurs at λ < 2, irrespective of the tested compression ratios. The Livenwood–Wu integral approach was evaluated to assess the likelihood of end-gas autoignition based on fuel reactivity, demonstrating that both normal and knocking combustion possibilities are consistent with experimental investigations. Combustion analysis at the ignition timing for maximum brake torque conditions demonstrates knock-free stable combustion up to λ = 3, with increased end-gas autoignition at lower λ values. To achieve knock-free combustion at those low λs, the spark timings are significantly retarded to after top dead center crank angle position. Engine-out NOx emissions consistently increase in trend with a decrease in the air–fuel ratio of up to λ = 3, after which a distinct variation in NOx is observed with an increase in the compression ratio.